SELECTIVE COLLECTION SOLIDARITY: AN EXPERIENCE DEVELOPED AT RESEARCH CAMPUS GOELDI MUSEUM (MPEG), BELÉM-PA - Nascimento, Rosana Oliveira; D’Aquino, Gilma Isabel Rêgo; Mendes, Amilcar Carvalho; Ruivo, Maria de Lourdes Pinheiro; Tashiro, Liane Hissae (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707889 This descriptive study reports a pilot experiment that aims to present the methodology used toimplement the Selective Collection Solidarity Program, at Research Campus in the Emilio GoeldiMuseum of Pará, as well as the main qualitative and quantitative results of recyclables produced at the institution. Data collection was conducted through a diagnosis of the situation andindividual semi-structured interviews with employees and outsourced employees working inhousekeeping, about the process of separation of recyclable materials, as was done to check theseparation, packaging and destination of these cooperatives. Seminar was held on the issue andtraining for contractors employees responsible for cleaning. The quantitative and qualitativeanalysis of recyclable materials produced in Campus Research was performed by separating,sorting and weighing of recyclable materials (paper, cardboard, plastics, glass and metals),produced under the research coordination and in the area outside the institution. The resultshowed that in the Research Campus is generated, annually, a load of recyclable waste fromapproximately 5,600 kg, which helps to benefit cooperatives that receive these materials. Theexperience subsidized the expansion of Selective Collection Solidarity Program to the otherphysical bases of the institution and especially to measure, even preliminarily, the contribution ofrecyclable materials produced within the institution and in the budget to improve the quality oflife of scavengers.